PENGARUH KOMPETENSI KARYAWAN TERHADAP PROMOSI JABATAN PADA PT BANK CIMB NIAGA tbk BINTARO GRIYA NIAGA - SUHA RINI RINI (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
Promotion of this position provides an important role for every employee, and became one of the always anticipated employees. Therefore, with this promotional target, employees feel appreciated, cared for, needed and recognized ability of work. One of the factors that influence the promotion of position is competence, strong employee competence is a very useful foundation to help companies improve their performance. The purpose of this research is to know the influence of employee competence (X variable) to promotion position (variable Y) at PT Bank CIMB Niaga Tbk Bintaro Griya Niaga. The data used are primary data obtained through observation method, interview method, questionnaire and documentation study. This research used slovin formula as sampling method with 48 respondents. The analysis of this research includes validity test, reliability test, correlation coefficient test, coefficient of determination test and simple linear regression equation test. Based on the result of the research, it can be seen that employee competence (X variable) has positive and significant influence on promotion of position (variable Y) at PT Bank CIMB Niaga Tbk Bintaro Griya Niaga with correlation coefficient 0,771, then coefficient of determination gives 50,6% promotion position while the remaining 49.4% influenced by other factors not examined. At the regression equation the value of a (constant) is 16,881 and the value of b (coefficient) is 0,815.   Key Word: ,employee competence, promotion of position